Impactos da implantação do PMO no desempenho da organização pública: o caso de uma instituição de ensino superior - Carvalho, Kahan Elizabeth Monteiro de (2013)
The field of project management is in full growth and the implementation of a Project Management Office (PMO) in a public institution of higher education (IPES) has the differential to unite effective practices of project management to scientific knowledge, technological and cultural produced by it, contributing to the achievement of positive results for society and for institutional strengthening. This work brings an experience of a public organization, from which was possible to present in detail the step by step of the project for implementation of its PMO, difficulties and facilities of the process, as well as the characteristics and the specific duties of the implemented project management office. In addition, the discussion on the special features of PMO of public administration and the presentation of the use of tools capable of measuring the impact of the actions of the new structure in the performance of permanent organization, compose a set of results and contributions not only applicable to other organizational contexts, but discuss with points already dealt with by the literature.Thus, the study proposes to contribute to the reduction of a gap in knowledge regarding how the PMO can contribute to the organizational performance in the public sector, by answering the following research question: "How does the deployment of a PMO impacts the organizational performance of public organization? ".For this reason, we used the scientific research applied with a qualitative approach, exploratory and applied the method of action research. This scientific methodology represents a type of social research with empirical base, designed and carried out by means of a action that is proposed to be applied to a collective problem, in which researchers are involved in a cooperative manner or participatory (Michel, 2009). The use of action research has enabled the correlation of theoretical framework studied with the action of deployment of the Project Management Office (EGP) of the Federal University of Juiz de Fora. The research ends up with the suggestion of a new flow chart for the deployment of a projects office; in the design of a matrix of impact assessment in the performance of the organization from the relationship between strategic alignment and investment in human capital, considered critical factors of success of the deployment; in the incorporation of the activities of collection of resources, planning of public projects and bidding processes, in its implementation; and, in a new reading of the five dimensions of success in projects defined by Shenhar and Dvir (2010). New highlights data were the deployment of the PMO in public organization, from the difficulties experienced by EGP-UFJF concerning the hiring of the team and the establishment of effective communication, both internally, considered the technical team of the project, and externally, whereas the relationship with the specialists, teachers of the institution. From the use of two tools of analysis of performance it was possible to measure and assert, consistently, that the PMO impacts the performance of public organization. The result reported by two tools used was broadly, especially considering the EGP-UFJF is a recent initiative that covers only part of the institutional mission of UFJF, but their results are potentially influenced by almost all of the essential aspects for an institution of higher education.